Penentuan Jumlah Produksi Garmen Dengan Metode Fuzzy Logic Mamdani - Rayhan, Rayhan; Firdayanti, Firdayanti; Sativa, Oktaryza; Shaum, Amien; Chairunnisa, Dwi Yulinar; Novianty, Inna (Jurnal Teknologi dan Riset Terapan (JATRA), 2023)
This study examines the determination of garment production quantities at PT. Istana Garmindo Jaya using the Fuzzy Mamdani method. Garment companies often face challenges in setting optimal production targets due to various complex factors such as fluctuating market demand and unstable raw material availability. The Fuzzy Mamdani method is employed to address this issue by generating accurate target production outputs. The research findings indicate a balance of control between production quantities, market demand, and raw material inventory. However, the differences between manual calculations and those using MATLAB software suggest that the determination of production quantities is still suboptimal and requires further improvement.